(untitled) (Journal of Contemporary Studies, 2023)
Pakistan has faced issues of religious radicalization, extremism and terrorism for decades; religious intolerance has not only transformed the social fabric of this society but has also divided its people into sectarian identities. Pakistan has adopted both kinetic and non-kinetic approaches to deal with these menaces of extremism and terrorism. On one side, the state has opted for kinetic options such as security operations to eliminate terrorism but it always comes back in some other form or place. On the other side, to eliminate this threat of violence, the state has opted for the use of non-kinetic approaches such as narratives and development/ education projects in the pockets of areas and social strata breeding extremism. This paper considers Paigham-e-Pakistan (Message of Pakistan) as an attempt to answer narratives of extremism, hatred, and intolerance and uproot them from the very foundations they claim to derive from religion. It aims to replace these divisive narratives with ideas of enlightenment and peace derived from the very same religion. This research is an attempt to understand the Paigham-e-Pakistan as a counter narrative document and to illustrate its importance within the Pakistani society.